Therapeutic effectiveness of iodine-rich herbs in treating Graves’ hyperthyroidism: a retrospective cohort study from a single center - Lai, Yiwen; Yang, Mengfei; Li, Jing; Gan, Di; Liu, Qingyang; Wang, Yingna; Gao, Tianshu (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the effectiveness of the traditional Chinese medicine decoction with iodine-rich herbs as the main agent (IRH) in patients with Graves’ hyperthyroidism (GD).MethodsA retrospective cohort study was conducted in a tertiary A traditional Chinese medicine hospital in northeastern China. We followed the effectiveness and safety of IRH in treating GD patients from January 2010 to August 2024 through the Intelligent Research Data Platform. Patients treated with IRH were classified into the IRH cohort, and those treated with antithyroid drugs (ATD) were classified into the ATD cohort. The characteristics of the two groups were balanced using propensity score matching (PSM). We used logistic regression, the Kaplan-Meier method, and the Cox proportional hazard model to compare the efficacy differences between IRH and ATD and to preliminarily identify the influencing factors of IRH efficacy through subgroup analysis of clinical characteristics.ResultsAfter screening and PSM, 73 GD patients treated with IRH and 73 with ATD were included in this study. IRH could significantly improve serum free T3 (fT3), free T4 (fT4), thyroid-stimulating hormone (TSH), and TSH receptor antibody (TRAb) levels in GD patients. Among the 73 patients who received IRH, the serum fT3, fT4, and TSH levels of 63 (86.3%), 65 (89%), and 40 (54.8%) patients, respectively, returned to normal, and the efficacy of IRH persisted for 50 (68.5%) patients. In addition, the median time to normalization and the regression analysis after correction for confounding factors did not show significant differences between IRH and ATD regarding efficacy and persistence. The safety evaluation results of the two drugs were similar. Higher IRH doses (>= 40g) may improve efficacy, while younger age, male gender, goiter, and more severe thyrotoxicosis might lead to poor efficacy of IRH.ConclusionCompared with ATD, IRH could also significantly improve the serum fT3, fT4, TSH, and TRAb levels of patients with GD and has a comparable duration of efficacy. For patients with mild to moderate GD, IRH provided a safe as well as effective alternative therapy.